Impurity binding energy for delta-doped quantum well structures (2014)
ABSTRACT: The binding energy of an impurity delta layer situated either in the centre or at the edge of a quantum well (QW) is theoretically considered for the example of n-type Si0⋅8Ge0⋅2/Si/Si0⋅8Ge0⋅2 QW doped with phosphorus. Calculations are made for the case of not so big impurity concentrations, when impurity bands are not yet formed and it is still possible to treat impurity as isolated ones. It is shown on the base of self-consistent solution of Schrödinger, Poisson and electro-neutrality equations that impurity binding energy is dependent on the degree of impurity ionization and the most noticeably for the case of edge-doped QWs.